2020
DOI: 10.1111/jphp.13221
|View full text |Cite
|
Sign up to set email alerts
|

Transport of trans-activator of transcription (TAT) peptide in tumour tissue model: evaluation of factors affecting the transport of TAT evidenced by flow cytometry

Abstract: Objectives Trans‐activator of transcription (TAT), a cell penetrating peptide, has been explored to overcome resistance to penetration and transport inside the cell, therefore, suggested to be used as drug delivery vector into drug‐resistant tumours. The generosity of this study was to evaluate modifiable factors (concentration, temperature, incubation time and spheroid age) on the penetration of TAT. Methods Multicellular tumour spheroids (MCTS) used as tumour tissue models to mimic some characteristics with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…[17][18][19] CPPs can penetrate the plasma membrane and the nucleus of almost any live cells. 20,21 As a kind of CPP, the transactivator of transcription (TAT) peptide has shown fast endosomal or lysosomal escape and quick nuclear localization, and can easily penetrate through biolm barriers like the BBB. 22,23 TAT and Ang can bind to DSPE-PEG 2000 -MAL with the cysteine structure through the MAL molecule group.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] CPPs can penetrate the plasma membrane and the nucleus of almost any live cells. 20,21 As a kind of CPP, the transactivator of transcription (TAT) peptide has shown fast endosomal or lysosomal escape and quick nuclear localization, and can easily penetrate through biolm barriers like the BBB. 22,23 TAT and Ang can bind to DSPE-PEG 2000 -MAL with the cysteine structure through the MAL molecule group.…”
Section: Introductionmentioning
confidence: 99%
“…As a commonly used CPP, trans-Activator of Transcription (TAT) protein was recently evaluated on solid tumors using the multicellular tumor spheroids as cell models. It showed that higher TAT concentrations significantly increased peptide uptake ( 51 ). In addition to TAT, penetratin, GALA, transportan, and its derivatives such as PepFect and NickFect have also received attention for their cell penetration abilities ( 52 ).…”
Section: Methodsmentioning
confidence: 99%
“…Some researchers are therefore designing techniques whereby the whole drug-nanoparticle structure may penetrate cancer cells before the actual release of pharmacological drugs into the cytosol to improve the accuracy of drug distribution to appropriate intracellular targets 108 , 109 . They are working to promote intracellular absorption by marking nanomaterials with peptides to penetrate the cells, like Penetration and anti-actin-targeting substances such as transcription transactivator (TAT) peptide in accompanying with a nice arrow peptide 110 , 111 . As most of the mentioned compounds have main objectives inside the cells, they are anticipated to have a stronger therapeutic impact.…”
Section: Nanostructures As Carriers For Drug Moleculesmentioning
confidence: 99%